Labour markets in terms of the fourth industrial revolution - Trenovski, Borce; Trpkova-nestorovska, Marija; Merdzan, Gunter; Kozheski, Kristijan (Faculty of Economic-Prilep, University St. Kliment Ohridski”-Bitola, 2020)
Recently, many studies and analysis confirmed that the world is at the beginning of a powerful process of transformation that will radically change our lives, ways of working and communicating.The Fourth Industrial Revolution is expected to improve the computerization of manufacturing industry and focuses on equipping the production with high technology. Three main goals of Industry 4.0 could be highlighted as: (1) Reduction of the human factor in manufacturing thus eliminating human errors. (2) Achieving high level of manufacturing flexibility and creating conditions for designing products that meet the specific requirements of the consumer. (3) Intensification of the production process.This paper aims to present the main trends in this field, to explain the benefits of technology and digitization for the global economy as well as to elaborate the importance of preparing different segments of society for effects from the Fourth Industrial Revolution onto the global labour market. This study obtains a panel data of six countries (France, Germany, Italy, Spain, UK and USA) for period between 1985 to 2017. The results have shown that information and communications technology and multifactor productivity are variables who have significant and positive impact on labour productivity while the variable average hours worked per person employed has a negative impact. Additional analysis of the demographic and socio-economic trends shows that the labour market will experience radical changes in the future.
Keywords: fourth Industrial Revolution, labour market, ICT, MFP